Pendidikan Antikorupsi : Peran Institusi Pendidikan dalam Membangun Integritas - Ulan Dari; Luna Erika Putri; Nadia Widyana Sari; Zulandi Adha; Rahma Marlia Sari; Nurhaliza Hersa Oktavia; Rikiawan Rikiawan (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Anti-corruption education is a strategic step in building the integrity of Indonesia's young generation, amidst widespread efforts to eradicate corruption which is detrimental to the economy and public trust. This service uses qualitative descriptive methods to explore the role of educational institutions in instilling anti-corruption values through innovative curricula and the use of digital technology. The aim of this journal is to increase awareness about the importance of anti-corruption education by utilizing digital technology, so that it can highlight the importance of anti-corruption education as part of a long-term solution to eradicating corruption, not just through law enforcement. This scientific work utilizes innovation by using digital technology, resulting in the finding that anti-corruption education can be successful with digital technology. This research provides a strong basis for education policies to strengthen anti-corruption culture systemically. The results of the service show that systemic integration of anti-corruption education can increase student understanding and build strong cultural integrity in the school environment..